Ethical issues raised by the introduction of payment for performance in France. Issue 8 (6th April 2012) - Saint-Lary, Olivier; Plu, Isabelle; Naiditch, Michel
Abstract : Context: In France, a new payment for performance (P4P) scheme for primary care physicians was introduced in 2009 through the 'Contract for Improving Individual Practice' programme. Its objective was to reduce healthcare expenditures while enhancing improvement in guidelines' observance. Nevertheless, in all countries where the scheme was implemented, it raised several concerns in the domain of professional ethics. Objective: To draw out in France the ethical tensions arising in the general practitioner's (GP) profession linked to the introduction of P4P. Method: Qualitative research using two focus groups: first one with a sample of GPs who joined P4P and second one with those who did not. All collective interviews were recorded and fully transcribed. An inductive analysis of thematic content with construction of categories was conducted. All the data were triangulated. Results: All participants agreed that conflicts of interest were a real issue, leading to the resurgence of doctor's dirigisme, which could be detrimental for patient's autonomy. GPs who did not join P4P believed that the scheme would lead to patient's selection while those who joined P4P did not. The level of the maximal bonus of the P4P was considered low by all GPs. This was considered as an offense by non-participating GPs, whereas for participating ones, this low level minimised the risk of patient's selection. Conclusion: This work identified several areas of ethical tension, some being different from those previously described in other countries. The authors discuss the potential impact of institutional contexts and variability of implementation processes on shaping these differences.